2019
DOI: 10.15171/jhp.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase inhibition by water-pepper (Polygonum hydropiper L.) sprout extract

Abstract: Introduction: Collagenase plays an important role in the degradation of dermal matrix proteins leading to wrinkle formation. The objectives of this study were to evaluate the inhibitory effect of water-pepper (Polygonum hydropiper L.) sprout extract on the activity of collagenase and to identify the inhibitory compounds.Methods: Collagenase inhibitory activity was measured by spectrophotometric assay. Activity-guided fractionation was performed using liquid-liquid extraction of water and n-butanol and Diaion H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Using essential oils extracted from some medicinal herbs and food plants, Aumeeruddy-Elalfi et al [22] demonstrated a minimal anti-collagenase activity and anti-elastase activity of 52.2% inhibition at 400 µg/mL and 32.23% inhibition at 800 mg/mL, respectively. A methanolic extract of water-pepper sprout inhibited collagenase activity in a concentration-dependent manner with an IC 50 value of 156.7 µg/mL [23].…”
Section: Discussionmentioning
confidence: 97%
“…Using essential oils extracted from some medicinal herbs and food plants, Aumeeruddy-Elalfi et al [22] demonstrated a minimal anti-collagenase activity and anti-elastase activity of 52.2% inhibition at 400 µg/mL and 32.23% inhibition at 800 mg/mL, respectively. A methanolic extract of water-pepper sprout inhibited collagenase activity in a concentration-dependent manner with an IC 50 value of 156.7 µg/mL [23].…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, N ‐ trans ‐caffeoyltyramine ( 8 ) was reported to exhibit 2,2‐diphenyl‐1‐picrylhydrazyl radical scavenging and low density lipoprotein oxidation suppression activities 69 . A previous report confirmed that quercetin 3′‐galactopyranoside ( 10 ) is effective toward the suppression of collagenase activity 70 . Therefore, 3 , 8 , and 10 are considered to be worth using as photoaging improvement materials.…”
Section: Resultsmentioning
confidence: 98%
“…69 A previous report confirmed that quercetin 3 0 -galactopyranoside (10) is effective toward the suppression of collagenase activity. 70 Therefore, 3, 8, and 10 are considered to be worth using as photoaging improvement materials. Compounds 1, 2, 4-7, 9, and 11 produced no observable improvement in cell activity against UVA-induced photodamage.…”
Section: Resultsmentioning
confidence: 99%
“…It is used to treat a variety of neurological disorders, including Alzheimer's disease (AD) (Ayaz et al 2016). It can be useful as a natural source of collagenase inhibitor that can be used to treat skin aging (Kawaguchi and Nagata 2019).…”
Section: Fabаceae Familymentioning
confidence: 99%